steel material

CN123022830APending Publication Date: 2026-10-30NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580023553.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-08
Filing Date
2025-02-28
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0046]本公开的钢材具有高强度、且即使在高H2S环境下也具有优异的耐SSC性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022830A_ABST
    Figure CN123022830A_ABST
Patent Text Reader

Abstract

Provided is a steel material having high strength and excellent SSC resistance in a high H2S environment. The steel material of the present disclosure, in terms of mass%, is C: 0.15% or more and less than 0.30%, Si: 0.05 to 1.00%, Mn: 0.05% or more and less than 0.30%, P: 0.020% or less, S: 0.0050% or less, Cr: 0.10 to 1.00%, Mo: 0.85 to 2.50%, Ti: 0.002 to 0.020%, Nb: 0.002 to 0.050%, V: 0.01 to 0.30%, Ca: 0.0001 to 0.0030%, B: 0.0005 to 0.0050%, Al: 0.005 to 0.100%, and the balance being Fe and impurities, the steel material having a yield strength of 862 MPa or more and less than 965 MPa, the content of elements, the grain size number GSN of prior austenite grains, and the P content P_seg. near prior austenite grain boundaries satisfying formula (1). (Mn + P_seg.) / (2.5Mo + GSN) ≤ 0.125 (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to steel, and more specifically, to steel suitable for use in high H2S environments. Background Technology

[0002] Due to the increasing depth of oil and gas wells (hereinafter, oil and gas wells are simply referred to as "oil wells"), there is a demand for high-strength steel for oil wells, represented by oil well steel pipes. Specifically, 80ksi grade (yield strength of 80ksi or higher and less than 95ksi, i.e., 552MPa or higher and less than 655MPa) and 95ksi grade (yield strength of 95ksi or higher and less than 110ksi, i.e., 655MPa or higher and less than 758MPa) oil well steel are widely used. Recently, there has been a further demand for 110ksi grade (yield strength of 110ksi or higher and less than 125ksi, i.e., 758MPa or higher and less than 862MPa) and 125ksi grade (yield strength of 125ksi or higher and less than 140ksi, i.e., 862MPa or higher and less than 965MPa) oil well steel pipes.

[0003] On the other hand, deep wells are mostly acidic environments containing corrosive hydrogen sulfide. In this specification, an acidic environment refers to an environment containing hydrogen sulfide and acidified. It should be noted that carbon dioxide is sometimes also present in acidic environments. Oil well steel pipes used in such acidic environments not only require high strength but also resistance to sulfide stress cracking (hereinafter referred to as SSC resistance).

[0004] Techniques for improving the strength and SSC resistance of steel are proposed in Japanese Patent Application Publication No. 2006-28612 (Patent Document 1) and Japanese Patent Application Publication No. 2017-166060 (Patent Document 2).

[0005] The steel disclosed in Patent Document 1 is a steel for steel pipes, which, by mass percent, comprises: C: 0.2-0.7%, Si: 0.01-0.8%, Mn: 0.1-1.5%, S: less than 0.005%, P: less than 0.03%, Al: 0.0005-0.1%, Ti: 0.005-0.05%, Ca: 0.0004-0.005%, N: less than 0.007%, Cr: 0.1-1.5%, Mo: 0.2-1.0%, with the balance being Fe and impurities. This steel also contains non-metallic inclusions of Ca, Al, Ti, N, O, and S, in which the (Ca%) / (Al%) ratio is 0.55-1.72 and the (Ca%) / (Ti%) ratio is 0.7-19. Patent Document 1 describes this steel as having a high yield strength exceeding 758 MPa and excellent resistance to SSC (Supersonic Sludge).

[0006] The steel disclosed in Patent Document 2 is a billet for high-strength oil well steel pipes, which, by mass%, comprises: C: 0.20~0.45%, Si: 0.05~0.40%, Mn: 0.3~0.9%, P: less than 0.015%, S: less than 0.005%, Al: 0.005~0.10%, N: 0.001~0.006%, Cr: 0.1~0.8%, Mo: 0.1~1.6%, V: 0.02~0.2%, Nb: 0.001~0.04%, B: 0.0003~0.0030%, O (oxygen): less than 0.0030%, with the balance being Fe and unavoidable impurities. The Rockwell hardness HRC of this steel also satisfies the formula (15.6×[%C]+29.2≤HRC<60.5×[%C]+31.1). Patent document 2 describes that, based on this steel, it is possible to obtain a steel pipe with a yield strength of 758 MPa or more and less than 862 MPa and excellent resistance to SSC.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2006-28612

[0010] Patent Document 2: Japanese Patent Application Publication No. 2017-166060 Summary of the Invention

[0011] The problem the invention aims to solve

[0012] Therefore, in recent years, wells operating in more severe environments have also attracted attention. For example, wells containing high-pressure hydrogen sulfide (H2S) gas have been developed. Specifically, under high-pressure acidic environments with a partial pressure of 10 atm H2S gas (hereinafter referred to as "high H2S environments"), more stringent SSC resistance is required than that of acidic environments containing H2S gas at atmospheric pressure. Therefore, steels with high SSC resistance even under such high H2S environments are sought.

[0013] Patent documents 1 and 2 mentioned above propose steels with high strength and excellent SSC resistance. However, neither patent document 1 nor 2 addresses SSC resistance in high H2S environments.

[0014] The purpose of this disclosure is to provide steel with high strength and excellent resistance to SSC even in high H2S environments.

[0015] Solution for solving the problem

[0016] The steel disclosed herein

[0017] In terms of mass %

[0018] C: Above 0.15% and below 0.30%

[0019] Si: 0.05~1.00%

[0020] Mn: ≥0.05% and <0.30%

[0021] P: below 0.020%

[0022] S: Below 0.0050%

[0023] Cr: 0.10~1.00%

[0024] Mo: 0.85~2.50%,

[0025] Ti: 0.002~0.020%

[0026] Nb: 0.002~0.050%

[0027] V: 0.01~0.30%,

[0028] Ca: 0.0001~0.0030%

[0029] B: 0.0005~0.0050%

[0030] Al: 0.005~0.100%

[0031] N: below 0.0050%

[0032] O: Below 0.0020%

[0033] Cu: 0~0.50%,

[0034] Ni: 0~0.50%

[0035] W: 0~1.00%

[0036] Zr: 0~0.50%,

[0037] Mg: 0~0.0100%

[0038] Rare earth elements: 0~0.0100%, and

[0039] The balance consists of Fe and impurities.

[0040] The yield strength of the steel is above 862 MPa and less than 965 MPa.

[0041] The content of the element, the grain size number GSN of the original austenite grains in the microstructure, and the P content P_seg near the original austenite grain boundary satisfy equation (1).

[0042] (Mn+P_seg.) / (2.5Mo+GSN)≤0.125 (1)

[0043] Here, the element symbols in equation (1) are replaced with the corresponding element content in the unit: mass%

[0044] In addition, in formula (1), the P content near the original austenite grain boundary is mol.% at P_seg. and the grain size number of the original austenite grain is substituted at GSN in formula (1).

[0045] The effects of the invention

[0046] The steel disclosed herein has high strength and excellent resistance to SSC even in high H2S environments. Attached Figure Description

[0047] Figure 1 This is a graph showing the relationship between Fn1 (=(Mn+P_seg.) / (2.5Mo+GSN)) in this embodiment and the number of SSC-generated roots (roots) as an indicator of SSC resistance. Detailed Implementation

[0048] First, the inventors considered obtaining steel with a yield strength of 125 ksi (862 MPa or more and less than 965 MPa), which is considered as high strength. Specifically, the inventors investigated and studied methods for obtaining a yield strength of 125 ksi and excellent resistance to SSC even in high H2S environments in steel intended for use in oil wells. As a result, the inventors obtained the following insights.

[0049] Next, the inventors focused on the grain boundaries of the original austenite grains (hereinafter, the original austenite grains will also be referred to as "original γ grains") and considered ways to improve the SSC resistance of steel. Here, if the original γ grain boundaries of the steel become embrittled and their crack susceptibility increases, the SSC resistance of the steel may decrease. On the other hand, if the embrittlement of the original γ grain boundaries of the steel can be suppressed and the original γ grain boundaries strengthened, it is possible to improve the SSC resistance of the steel.

[0050] Here, manganese (Mn) in the chemical composition tends to accumulate at the proto-γ grain boundaries, easily causing them to become embrittled. Mn further promotes the accumulation of phosphorus (P) at the proto-γ grain boundaries, further embrittlement. On the other hand, if molybdenum (Mo) accumulates at the proto-γ grain boundaries, it can strengthen them. Based on the research results of the inventors, it is shown that if the Mn content of the steel is reduced to less than 0.30% and the Mo content is increased to more than 0.85%, the embrittlement of the proto-γ grain boundaries in the steel can be suppressed, and the proto-γ grain boundaries of the steel can be strengthened.

[0051] That is, the inventors believe that the following steel, by mass percent: C: 0.15% or more and less than 0.30%, Si: 0.05% to 1.00%, Mn: 0.05% or more and less than 0.30%, P: 0.02% or less, S: 0.0050% or less, Cr: 0.10% to 1.00%, Mo: 0.85% to 2.50%, Ti: 0.002% to 0.020%, Nb: 0.002% to 0.050%, V: 0.01% to 0.30%, Ca: 0.000% to 0.000% is suitable. With 1~0.0030%, B: 0.0005~0.0050%, Al: 0.005~0.100%, N: less than 0.0050%, O: less than 0.0020%, Cu: 0~0.50%, Ni: 0~0.50%, W: 0~1.00%, Zr: 0~0.50%, Mg: 0~0.0100%, rare earth elements: 0~0.0100%, and the balance being Fe and impurities, it is possible to achieve a yield strength of 125 ksi and excellent resistance to SSC.

[0052] On the other hand, even with the above-mentioned chemical composition, excellent SSC resistance is sometimes not achieved in high H2S environments. Therefore, the inventors further investigated in detail the factors that reduce SSC resistance in the above-mentioned steel under high H2S environments. The results showed that, even for steels with the above-mentioned chemical composition, the effect of embrittlement of the proto-γ grain boundaries becomes significant in high H2S environments, and the SSC resistance of the steel is easily reduced. Therefore, the inventors conducted a detailed study on further proto-γ grain boundary strengthening of steels with the above-mentioned chemical composition.

[0053] The results of the detailed research conducted by the inventors show that in steel with the above chemical composition, if the Mn content, Mo content, grain size number GSN of the original γ grain and the P content P_seg near the original γ grain boundary in the steel satisfy the following formula (1), then it is possible to stably balance the yield strength of 125 ksi and the resistance to SSC in a high H2S environment.

[0054] (Mn+P_seg.) / (2.5Mo+GSN)≤0.125 (1)

[0055] Here, the element symbols in Equation (1) are substituted with the corresponding element content in the unit: mass% . In addition, the P content near the original austenite grain boundary is substituted with mol.% in Equation (1), and the grain size number of the original austenite grain is substituted with GSN in Equation (1).

[0056] Fn1 is defined as Fn1 = (Mn + P_seg.) / (2.5Mo + GSN). The following figures illustrate the relationship between Fn1 and SSC resistance in high H2S environments in more detail. Figure 1 This is a graph showing the relationship between Fn1 (=(Mn+P_seg.) / (2.5Mo+GSN)) in this embodiment and the number of SSC-generated roots (roots) as an indicator of SSC resistance. Figure 1 It is made by using the Fn1 obtained by the method described later and the number of SSCs generated in an H2S gas environment of 10 atm obtained by the method described later, which are steels having the above chemical composition and a yield strength of 862 MPa or more and less than 965 MPa in the embodiments described later.

[0057] Reference Figure 1 In steels with the aforementioned chemical composition and a yield strength of 862 MPa or higher but less than 965 MPa, if Fn1 is 0.125 or lower, the number of SSCs generated in a 10 atm H2S gas environment is zero, exhibiting excellent SSC resistance even in high H2S environments. Conversely, in steels with the aforementioned chemical composition and a yield strength of 862 MPa or higher but less than 965 MPa, if Fn1 exceeds 0.125, the number of SSCs generated in a 10 atm H2S gas environment is one or more, and excellent SSC resistance is not observed in high H2S environments. Therefore, the steel of this embodiment, based on the aforementioned chemical composition and a yield strength of 862 MPa or higher but less than 965 MPa, has Fn1 of 0.125 or lower. As a result, the steel of this embodiment exhibits high strength and excellent SSC resistance even in high H2S environments.

[0058] It should be noted that, regarding the reasons why steels with the above-mentioned chemical composition and a yield strength of 862 MPa or higher but less than 965 MPa exhibit excellent SSC resistance even in high H2S environments if Fn1 is 0.125 or lower, the details are not yet clear. However, the inventors speculate as follows. Here, Fn1 (=(Mn+P_seg.) / (2.5Mo+GSN)) is an indicator of the degree of embrittlement of the proto-γ grain boundary. As mentioned above, the higher the Mn content, the more Mn is enriched at the proto-γ grain boundary, and the more easily the proto-γ grain boundary becomes embrittled. In addition, the higher the P content P_seg. near the proto-γ grain boundary (hereinafter, the P content P_seg. near the proto-γ grain boundary will also be referred to as "grain boundary P amount P_seg."), the more easily the proto-γ grain boundary becomes embrittled.

[0059] On the other hand, the higher the Mo content, the more Mo is enriched at the proto-γ grain boundaries, which can strengthen them. Furthermore, the larger the grain size number (GSN) of the proto-γ grains, the smaller the grain diameter, and the larger the area occupied by the proto-γ grain boundaries in the steel, potentially mitigating the embrittlement of the proto-γ grain boundaries. Therefore, the inventors hypothesize that, given the above-described chemical composition and a yield strength of 862 MPa or more but less than 965 MPa, excellent SSC resistance can be stably obtained even in high H2S environments by setting Fn1 to 0.125 or less. It should be noted that, based on a mechanism different from the inventors' hypothesis, excellent SSC resistance can be stably obtained even in high H2S environments. However, the examples described later demonstrate that, given the above-described chemical composition and a yield strength of 862 MPa or more but less than 965 MPa, excellent SSC resistance can be obtained even in high H2S environments by setting Fn1 to 0.125 or less.

[0060] The main points of the steel used in this embodiment, based on the above insights, are as follows. [1]

[0062] A type of steel, which is expressed as a percentage by mass.

[0063] C: Above 0.15% and below 0.30%

[0064] Si: 0.05~1.00%

[0065] Mn: ≥0.05% and <0.30%

[0066] P: below 0.020%

[0067] S: Below 0.0050%

[0068] Cr: 0.10~1.00%

[0069] Mo: 0.85~2.50%,

[0070] Ti: 0.002~0.020%

[0071] Nb: 0.002~0.050%

[0072] V: 0.01~0.30%,

[0073] Ca: 0.0001~0.0030%

[0074] B: 0.0005~0.0050%

[0075] Al: 0.005~0.100%

[0076] N: below 0.0050%

[0077] O: Below 0.0020%

[0078] Cu: 0~0.50%,

[0079] Ni: 0~0.50%

[0080] W: 0~1.00%

[0081] Zr: 0~0.50%,

[0082] Mg: 0~0.0100%

[0083] Rare earth elements: 0~0.0100%, and

[0084] The balance consists of Fe and impurities.

[0085] The yield strength of the steel is above 862 MPa and less than 965 MPa.

[0086] The content of the element, the grain size number GSN of the original austenite grains in the microstructure, and the P content P_seg near the original austenite grain boundary satisfy equation (1).

[0087] (Mn+P_seg.) / (2.5Mo+GSN)≤0.125 (1)

[0088] Here, the element symbols in Equation (1) are substituted with the corresponding element content in the unit: mass% . In addition, the P content near the original austenite grain boundary is substituted with mol.% in P_seg. in Equation (1), and the grain size number of the original austenite grain is substituted with GSN in Equation (1). [2]

[0090] According to the steel described in [1], it contains selected free...

[0091] Cu: 0.01~0.50%,

[0092] Ni: 0.01~0.50%

[0093] W: 0.01~1.00%

[0094] Zr: 0.01~0.50%,

[0095] Mg: 0.0001~0.0100%, and

[0096] Rare earth elements: one or more elements in a group consisting of 0.0001 to 0.0100%. [3]

[0098] According to the steel described in [1] or [2], wherein,

[0099] The steel is a seamless steel pipe.

[0100] The shape of the steel used in this embodiment is not particularly limited. The steel can be a steel pipe, a round bar (solid), or a steel plate. It should be noted that round bar refers to a bar with a circular cross-section perpendicular to the axial direction. Additionally, the steel pipe can be a seamless steel pipe or a welded steel pipe.

[0101] The steel used in this embodiment will be described in detail below. Unless otherwise specified, "%" related to elements refers to mass%.

[0102] [Chemical Composition]

[0103] The steel in this embodiment contains the following elements in its chemical composition.

[0104] C: Above 0.15% and less than 0.30%

[0105] Carbon (C) improves the hardenability and strength of steel. If the C content is too low, the above-mentioned effects cannot be fully achieved even if the contents of other elements are within the range of this embodiment. On the other hand, if the C content is too high, excessive carbides will be generated in the steel even if the contents of other elements are within the range of this embodiment, reducing the steel's resistance to SSC. Therefore, the C content is 0.15% or more and less than 0.30%. The preferred lower limit of the C content is 0.16%, more preferably 0.17%. The preferred upper limit of the C content is 0.29%, more preferably 0.28%, and more preferably 0.27%.

[0106] Si: 0.05~1.00%

[0107] Silicon (Si) deoxidizes steel. If the Si content is too low, the aforementioned effect cannot be fully achieved even if the contents of other elements are within the range of this embodiment. On the other hand, if the Si content is too high, the SSC resistance of the steel decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Si content is 0.05 to 1.00%. The preferred lower limit of the Si content is 0.06%, more preferably 0.08%, and even more preferably 0.10%. The preferred upper limit of the Si content is 0.96%, more preferably 0.92%, and even more preferably 0.90%.

[0108] Mn: ≥0.05% and <0.30%

[0109] Manganese (Mn) improves the hardenability and strength of steel. If the Mn content is too low, the above-mentioned effects cannot be fully achieved even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mn content is too high, the original γ grain boundaries become embrittled even if the contents of other elements are within the range of this embodiment, and the SSC resistance of the steel decreases. If the Mn content is too high, it further promotes the increase of grain boundary phosphorus content (P_seg.), and the SSC resistance of the steel decreases. Therefore, the Mn content is 0.05% or more and less than 0.30%. The preferred lower limit of the Mn content is 0.06%, more preferably 0.08%, and more preferably 0.10%. The preferred upper limit of the Mn content is 0.29%, and more preferably 0.28%.

[0110] P: below 0.020%

[0111] Phosphorus (P) is an impurity. That is, the lower limit of P content exceeds 0%. If the P content is too high, even if the contents of other elements are within the range of this embodiment, the grain boundary P content (P_seg.) becomes too high, and the SSC resistance of the steel decreases. Therefore, the P content is 0.020% or less. The preferred upper limit of P content is 0.018%, more preferably 0.015%. The P content is preferably as low as possible. However, an extreme reduction in P content would significantly increase manufacturing costs. Therefore, considering industrial production, the preferred lower limit of P content is 0.001%, more preferably 0.002%, and more preferably 0.003%.

[0112] S: Below 0.0050%

[0113] Sulfur (S) is an impurity. That is, the lower limit of S content exceeds 0%. If the S content is too high, even if the contents of other elements are within the range of this embodiment, coarse sulfide inclusions will be formed, reducing the SSC resistance of the steel. Therefore, the S content is 0.0050% or less. The preferred upper limit of S content is 0.0045%, more preferably 0.0040%, and even more preferably 0.0035%. The S content is preferably as low as possible. However, an extreme reduction in S content would significantly increase manufacturing costs. Therefore, considering industrial production, the preferred lower limit of S content is 0.0001%, more preferably 0.0002%, and even more preferably 0.0003%.

[0114] Cr: 0.10~1.00%

[0115] Chromium (Cr) improves the hardenability and strength of steel. If the Cr content is too low, the above-mentioned effects cannot be fully achieved even if the contents of other elements are within the range of this embodiment. On the other hand, if the Cr content is too high, the strength of the steel becomes too high even if the contents of other elements are within the range of this embodiment, and the steel's resistance to SSC decreases. Therefore, the Cr content is 0.10 to 1.00%. The preferred lower limit of the Cr content is 0.15%, more preferably 0.20%. The preferred upper limit of the Cr content is 0.95%, more preferably 0.90%, more preferably 0.85%, and more preferably 0.80%.

[0116] Mo: 0.85~2.50%

[0117] Molybdenum (Mo) is enriched at the original γ grain boundaries, strengthening them. As a result, the steel's resistance to SSC (Self-Containing Steel Staining) is improved. If the Mo content is too low, the above-mentioned effect cannot be fully obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mo content is too high, fine carbides are excessively formed even if the contents of other elements are within the range of this embodiment, resulting in excessively high strength of the steel and reduced SSC resistance. Therefore, the Mo content is 0.85~2.50%. The preferred lower limit of the Mo content is 0.87%, more preferably 0.90%. The preferred upper limit of the Mo content is 2.20%, more preferably 2.00%.

[0118] Ti: 0.002~0.020%

[0119] Titanium (Ti) forms fine nitrides, which refine the original γ-grain of the steel through a pinning effect. As a result, the grain size number (GSN) of the original γ-grain increases, and the SSC resistance of the steel improves. If the Ti content is too low, the above-mentioned effect cannot be fully obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Ti content is too high, coarse nitrides will be formed even if the contents of other elements are within the range of this embodiment, and the SSC resistance of the steel will decrease. Therefore, the Ti content is 0.002~0.020%. The preferred lower limit of the Ti content is 0.003%, more preferably 0.005%. The preferred upper limit of the Ti content is 0.018%, more preferably 0.016%, and more preferably 0.014%.

[0120] Nb: 0.002~0.050%

[0121] Niobium (Nb) forms carbides, nitrides, or carbonitrides (hereinafter referred to as "carbonitrides, etc."), which refine the original γ-grain of the steel through a pinning effect. As a result, the grain size number (GSN) of the original γ-grain increases, and the SSC resistance of the steel improves. If the Nb content is too low, the above-mentioned effect cannot be fully obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Nb content is too high, carbonitrides, etc., will be generated excessively even if the contents of other elements are within the range of this embodiment, and the SSC resistance of the steel will decrease. Therefore, the Nb content is 0.002 to 0.050%. The preferred lower limit of the Nb content is 0.003%, more preferably 0.005%. The preferred upper limit of the Nb content is 0.045%, more preferably 0.040%.

[0122] V: 0.01~0.30%

[0123] Vanadium (V) forms carbonitrides and other compounds, increasing the strength of steel. If the V content is too low, the aforementioned effects cannot be fully achieved even if the contents of other elements are within the range of this embodiment. On the other hand, if the V content is too high, the strength of the steel becomes excessively high even if the contents of other elements are within the range of this embodiment, and the steel's resistance to SSC decreases. Therefore, the V content is 0.01 to 0.30%. The preferred lower limit of the V content is 0.02%, more preferably 0.03%, and even more preferably 0.05%. The preferred upper limit of the V content is 0.28%, more preferably 0.25%, and even more preferably 0.22%.

[0124] Ca: 0.0001~0.0030%

[0125] Calcium (Ca) forms sulfides, reducing the amount of Mn sulfides at the original γ grain boundaries. As a result, the SSC resistance of the steel is improved. If the Ca content is too low, the above-mentioned effect cannot be fully obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Ca content is too high, coarse oxides will be formed even if the contents of other elements are within the range of this embodiment, and the SSC resistance of the steel will decrease. Therefore, the Ca content is 0.0001~0.0030%. The preferred lower limit of the Ca content is 0.0003%, more preferably 0.0005%. The preferred upper limit of the Ca content is 0.0028%, more preferably 0.0025%.

[0126] B: 0.0005~0.0050%

[0127] Boron (B) improves the hardenability and strength of steel. B further enriches at the original γ grain boundaries, reducing the amount of phosphorus (P_seg.) at the grain boundaries. As a result, the steel's resistance to saturation corrosion cracking (SSC) is improved. If the B content is too low, the above-mentioned effects cannot be fully achieved even if the contents of other elements are within the range of this embodiment. On the other hand, if the B content is too high, coarse B nitrides will be formed even if the contents of other elements are within the range of this embodiment, reducing the steel's resistance to SSC. Therefore, the B content is 0.0005~0.0050%. The preferred lower limit of the B content is 0.0006%, more preferably 0.0008%, and even more preferably 0.0010%. The preferred upper limit of the B content is 0.0048%, and even more preferably 0.0045%.

[0128] Al: 0.005~0.100%

[0129] Aluminum (Al) deoxidizes steel. If the Al content is too low, the aforementioned effect cannot be fully achieved even if the contents of other elements are within the range of this embodiment. On the other hand, if the Al content is too high, coarse oxide inclusions will be generated even if the contents of other elements are within the range of this embodiment, reducing the SSC resistance of the steel. Therefore, the Al content is 0.005 to 0.100%. The preferred lower limit of the Al content is 0.005%, more preferably 0.010%, more preferably 0.015%, and more preferably 0.020%. The preferred upper limit of the Al content is 0.090%, more preferably 0.080%, more preferably 0.070%, more preferably 0.065%, and more preferably 0.060%. The "Al" content mentioned in this specification refers to the content of "acid-soluble Al," i.e., "sol.Al."

[0130] N: below 0.0050%

[0131] Nitrogen (N) is unavoidably present. That is, the lower limit of N content exceeds 0%. N forms nitrides, which refine the original γ-grain of the steel through a pinning effect. As a result, the grain size number (GSN) of the original γ-grain increases, and the SSC resistance of the steel improves. On the other hand, if the N content is too high, even if the contents of other elements are within the range of this embodiment, coarse nitrides will be formed, and the SSC resistance of the steel will decrease. Therefore, the N content is 0.0050% or less. The preferred upper limit of N content is 0.0048%, more preferably 0.0045%, and even more preferably 0.0040%. The preferred lower limit of N content for more effectively obtaining the above-mentioned effect is 0.0003%, more preferably 0.0005%, and even more preferably 0.0010%.

[0132] O: Below 0.0020%

[0133] Oxygen (O) is an unavoidable impurity. That is, the lower limit of O content exceeds 0%. If the O content is too high, even if the contents of other elements are within the range of this embodiment, coarse oxides will form, reducing the steel's resistance to SSC. Therefore, the O content is 0.0020% or less. The preferred upper limit of O content is 0.0018%, more preferably 0.0015%. The O content is preferably as low as possible. However, extreme reductions in O content would significantly increase manufacturing costs. Therefore, considering industrial production, the preferred lower limit of O content is 0.0001%, more preferably 0.0005%, and even more preferably 0.0008%.

[0134] The steel in this embodiment has a chemical composition balance of Fe and impurities. Here, impurities refer to substances that are permissible during the industrial manufacturing of steel, which may be introduced from the ore, waste, or manufacturing environment used as raw materials, and are within the range that do not adversely affect the steel of this embodiment.

[0135] [Any element]

[0136] The chemical composition of the aforementioned steel may also contain one or more elements selected from the group consisting of Cu and Ni to replace a portion of the Fe. These elements are arbitrary and improve the hardenability and strength of the steel.

[0137] Cu: 0~0.50%

[0138] Copper (Cu) can be any element, or it can be absent. That is, the Cu content can be 0%. When present, Cu improves the hardenability and strength of the steel. Even a small amount of Cu is sufficient to achieve these effects. However, if the Cu content is too high, the hardenability of the steel will become excessive, even if the contents of other elements are within the range of this embodiment, and the steel's resistance to SSC will decrease. Therefore, the Cu content is 0 to 0.50%. The preferred lower limit of the Cu content is more than 0%, more preferably 0.01%, and more preferably 0.02%. The preferred upper limit of the Cu content is 0.40%, more preferably 0.30%, more preferably 0.20%, and more preferably 0.10%.

[0139] Ni: 0~0.50%

[0140] Nickel (Ni) is an arbitrary element and may be absent. That is, the Ni content can be 0%. When present, Ni improves the hardenability and strength of the steel. Ni also dissolves in the steel, thus improving its toughness. These effects are achieved to some extent with only a small amount of Ni. However, if the Ni content is too high, even if the contents of other elements are within the range of this embodiment, it will promote localized corrosion and reduce the steel's resistance to SSC. Therefore, the Ni content is 0 to 0.50%. The preferred lower limit of the Ni content is more than 0%, more preferably 0.01%, more preferably 0.02%, and more preferably 0.04%. The preferred upper limit of the Ni content is 0.40%, more preferably 0.30%, more preferably 0.20%, and more preferably 0.10%.

[0141] The chemical composition of the aforementioned steel may also contain W to replace a portion of Fe.

[0142] W: 0~1.00%

[0143] Tungsten (W) can be any element, or it can be absent. That is, the W content can be 0%. When present, W forms a protective corrosion coating in an acidic environment, inhibiting the intrusion of hydrogen into the steel. As a result, the steel's resistance to SSC is improved. The above-mentioned effect is achieved to some extent even with only a small amount of W. However, if the W content is too high, coarse carbides will form in the steel, even if the contents of other elements are within the range of this embodiment, reducing the steel's low-temperature toughness and SSC resistance. Therefore, the W content is 0 to 1.00%. The preferred lower limit of the W content is more than 0%, more preferably 0.01%, more preferably 0.03%, more preferably 0.05%, and more preferably 0.10%. The preferred upper limit of the W content is 0.90%, more preferably 0.80%, more preferably 0.60%, and more preferably 0.50%.

[0144] The chemical composition of the aforementioned steel may also contain one or more elements selected from the group consisting of Zr, Mg, and rare earth elements to replace a portion of the Fe. These elements are arbitrary and neutralize the S in the steel in the form of sulfides, thereby improving the steel's resistance to SSC.

[0145] Zr: 0~0.50%

[0146] Zirconium (Zr) can be any element, or it can be absent. That is, the Zr content can be 0%. When present, Zr neutralizes sulfur in the steel in the form of sulfides, improving the steel's resistance to sulfur oxides (SSCs). Even a small amount of Zr is sufficient to achieve the above-mentioned effect. However, if the Zr content is too high, even if the contents of other elements are within the range of this embodiment, the oxides in the steel will become coarser, reducing the steel's SSC resistance. Therefore, the Zr content is 0 to 0.50%. The preferred lower limit of the Zr content is more than 0%, more preferably 0.01%, and more preferably 0.03%. The preferred upper limit of the Zr content is 0.40%, more preferably 0.30%, more preferably 0.20%, and more preferably 0.10%.

[0147] Mg: 0~0.0100%

[0148] Magnesium (Mg) can be any element, or it can be absent. That is, the Mg content can be 0%. When present, Mg neutralizes sulfur (S) in the steel as sulfides, improving the steel's resistance to sulfur oxides (SSCs). Even a small amount of Mg is sufficient to achieve the above-mentioned effect. However, if the Mg content is too high, even if the contents of other elements are within the range of this embodiment, the oxides in the steel will become coarser, reducing the steel's SSC resistance. Therefore, the Mg content is 0 to 0.0100%. The preferred lower limit of the Mg content is over 0%, more preferably 0.0001%, more preferably 0.0005%, more preferably 0.0010%, and more preferably 0.0020%. The preferred upper limit of the Mg content is 0.0090%, more preferably 0.0080%, more preferably 0.0070%, more preferably 0.0060%, and more preferably 0.0050%.

[0149] Rare earth elements (REM): 0~0.0100%

[0150] Rare earth elements (REMs) can be any element, or they can be absent. That is, the REM content can be 0%. When present, REMs neutralize sulfur in the steel in the form of sulfides, improving the steel's resistance to sulfur dioxide (SSC). Even a small amount of REMs is sufficient to achieve the above-mentioned effect. However, if the REM content is too high, even if the contents of other elements are within the range of this embodiment, the oxides in the steel will become coarser, reducing the steel's resistance to SSC. Therefore, the REM content is 0 to 0.0100%. The preferred lower limit of the REM content is more than 0%, more preferably 0.0001%, more preferably 0.0005%, more preferably 0.0010%, and more preferably 0.0020%. The preferred upper limit of the REM content is 0.0090%, more preferably 0.0080%, more preferably 0.0070%, and more preferably 0.0060%.

[0151] It should be noted that REM in this specification refers to one or more elements selected from the group consisting of scandium (Sc) atomic number 21, yttrium (Y) atomic number 39, and lanthanum (La) atomic number 57 to lutetium (Lu) atomic number 71, which are lanthanide elements. Furthermore, REM content in this specification refers to the total content of these elements.

[0152] [Yield Strength]

[0153] The steel used in this embodiment has a yield strength of 862 MPa or more and less than 965 MPa (125 ksi or more and less than 140 ksi). The yield strength referred to in this specification means the stress at 0.7% elongation obtained in a tensile test according to ASTM E8 / E8M (2022).

[0154] The yield strength of the steel in this embodiment is determined by the following method. Specifically, tensile test pieces are made from the steel of this embodiment. When the steel is a steel plate, a tensile test piece is made from the center of the plate thickness. In this case, the long side direction of the tensile test piece is parallel to the rolling direction of the steel plate. When the steel is a steel pipe, a tensile test piece is made from the center of the wall thickness. In this case, the long side direction of the tensile test piece is parallel to the pipe axis direction. When the steel is a round bar, a tensile test piece is made at the R / 2 position. In this specification, the R / 2 position of the round bar refers to the center position of radius R in a section perpendicular to the axial direction of the round bar. In this case, the long side direction of the tensile test piece is parallel to the axial direction of the round bar.

[0155] The tensile test specimen is, for example, a round bar specimen with a parallel section diameter of 8.9 mm and a gauge length of 35.6 mm. When the steel is a steel pipe, an arc-shaped specimen can be used as the tensile test specimen. In this case, the size of the arc-shaped specimen is, for example, the thickness of the total wall thickness, the width of 25.4 mm, and the gauge length of 50.8 mm. The long side of the arc-shaped specimen is parallel to the pipe axis. Using the prepared tensile test specimen, a tensile test according to ASTM E8 / E8M (2022) is performed at room temperature (25°C) in the atmosphere. The stress at 0.7% elongation obtained through the tensile test is defined as the yield strength (MPa). It should be noted that in this embodiment, the yield strength (MPa) is obtained by rounding the first decimal place.

[0156] [Fn1]

[0157] The steel in this embodiment has the above-mentioned chemical composition, and the content of elements, the grain size number GSN of the original austenite grains in the microstructure, and the P content P_seg near the original austenite grain boundary satisfy equation (1).

[0158] (Mn+P_seg.) / (2.5Mo+GSN)≤0.125 (1)

[0159] Here, the element symbols in Equation (1) are substituted with the corresponding element content in the unit: mass% . In addition, the P content near the original austenite grain boundary is substituted with mol.% in Equation (1), and the grain size number of the original austenite grain is substituted with GSN in Equation (1).

[0160] As mentioned above, the phosphorus content (P_seg.) near the proto-γ grain boundary is also called the "grain boundary phosphorus content (P_seg.)". Furthermore, Fn1 (=(Mn+P_seg.) / (2.5Mo+GSN)) is an indicator of the degree of embrittlement of the proto-γ grain boundary. The higher the Mn content, the more Mn is enriched at the proto-γ grain boundary, and the more easily the proto-γ grain boundary becomes embrittled. Similarly, the higher the grain boundary phosphorus content (P_seg.), the more easily the proto-γ grain boundary becomes embrittled. On the other hand, the higher the Mo content, the more Mo is enriched at the proto-γ grain boundary, which strengthens the proto-γ grain boundary. Furthermore, the larger the grain size designation (GSN) of the proto-γ grain, the smaller the grain diameter of the proto-γ grain, and the larger the area occupied by the proto-γ grain boundary in the steel, which helps to mitigate the embrittlement of the proto-γ grain boundary.

[0161] That is, the steel of this embodiment does not simply refine the original γ grains or reduce the amount of phosphorus (P) at the grain boundaries. Instead, it adjusts the content of Mn, the element that embrittles the original γ grain boundaries, the content of Mo, the element that strengthens the original γ grain boundaries, the grain size designation (GSN) of the original γ grains, and the amount of phosphorus (P_seg) at the grain boundaries. As a result, the steel of this embodiment can stably maintain a yield strength of 125 ksi and excellent resistance to saturated carbon dioxide (SSC) even in high H2S environments.

[0162] The preferred upper limit for Fn1 is 0.124, and more preferably 0.122. The lower limit for Fn1 is not particularly limited. On the other hand, in steels having the above chemical composition, the lower limit for Fn1 can be, for example, 0.060, 0.080, or 0.090.

[0163] The grain size designation GSN of the original γ grains only needs to satisfy formula (1) and is not particularly limited. On the other hand, in steel having the above chemical composition and satisfying formula (1), the grain size designation GSN of the original γ grains is, for example, 5.0 to 12.0. The preferred lower limit of the grain size designation GSN of the original γ grains is 5.5, and more preferably 6.0. The upper limit of the grain size designation GSN of the original γ grains can be 11.5 or 11.0.

[0164] The P content (grain boundary P amount) P_seg. near the original γ grain boundary is not particularly limited as long as it satisfies formula (1). On the other hand, in steel having the above chemical composition and satisfying formula (1), the grain boundary P amount P_seg. is, for example, 1.7 mol.% or less. The preferred upper limit of the grain boundary P amount P_seg. is 1.6 mol.%, more preferably 1.5 mol.%. The lower limit of the grain boundary P amount P_seg. can be 0.0 mol.%, 0.3 mol.%, 0.5 mol.%, or 1.0 mol.%.

[0165] In this embodiment, Fn1 can be determined by the following method. First, the original γ grain size number GSN of the steel of this embodiment is determined. Specifically, a test piece for measuring the original γ grain size D is made from the steel of this embodiment. When the steel is a steel plate, a test piece is made from the center of the plate thickness, with a surface including the rolling direction and the plate thickness direction as the observation surface. When the steel is a steel pipe, a test piece is made from the center of the wall thickness, with a surface including the pipe axis direction and the pipe diameter direction as the observation surface. When the steel is a round bar, a test piece is made with a surface including the R / 2 position in the center and including both axial and radial directions as the observation surface.

[0166] The test piece is embedded in resin, and the observation surface is polished to a mirror finish. It is then immersed in a solution of a suitable amount of surfactant mixed with a saturated aqueous solution of picric acid for approximately 60 seconds, revealing the original γ grain boundaries through etching. The area of ​​the observation surface is not limited; for example, it can be set to 100 mm². 2 (10mm × 10mm). The grain size number GSN was determined by observation under an optical microscope based on the cutting method according to JIS G 0551 (2020). It should be noted that in this embodiment, the grain size number GSN of the original γ grain was obtained by rounding the second decimal place of the obtained value.

[0167] Next, the grain boundary P-value P_seg. of the steel in this embodiment is determined. Specifically, a notched round bar test piece is made from the steel in this embodiment. The size of the notched round bar test piece is, for example, 3 mm in diameter and 17 mm in axial length. Furthermore, the notch is formed at the center of the axial length of the round bar test piece. The notch is, for example, a V-shaped notch with a depth of 0.7 mm, formed around the entire circumference of the round bar. When the steel is a steel plate, the test piece is made from the center of the plate thickness. In this case, the axial direction of the test piece is set parallel to the rolling direction of the steel plate. When the steel is a steel pipe, the test piece is made from the center of the wall thickness. In this case, the axial direction of the test piece is set parallel to the pipe axis direction of the steel pipe. When the steel is a round bar, the test piece is made from the R / 2 position. In this case, the axial direction of the test piece is set parallel to the axial direction of the round bar.

[0168] The prepared test piece was placed in the vacuum chamber of the Auger electron spectroscopy analyzer, and the vacuum level inside the chamber was set to 10. -7 Below Pa. An Auger electron spectroscopy analyzer, for example, ULVAC-PHI, Inc. (PHI680), is used. The test piece, cooled to below -120°C, is subjected to impact fracture within the chamber to obtain the original γ-grain boundary fracture. In this embodiment, multiple measurement points are determined from multiple original γ-grain boundary fractures. Specifically, for example, a total of 10 or more measurement points are determined from 3 or more original γ-grain boundary fractures. Furthermore, the measurement points determined here are the regions within the original γ-grain boundary fractures excluding precipitates. Those skilled in the art can determine whether it is a precipitate based on the contrast.

[0169] Elemental concentration analysis based on Auger electron spectroscopy was performed at the determined measurement points. In Auger electron spectroscopy, the accelerating voltage was set to 10 kV and the sample current to 10 nA, and the target elements were P, S, C, Cr, Fe, Mn, Si, and Mo for quantification. In differential Auger spectroscopy, the Auger peaks for each element used in the quantitative calculations were set as follows: P: 102–130 eV, S: 131–165 eV, C: 234–292 eV, Cr: 510–540 eV, Fe: 685–715 eV, Mn: 535–545 eV, Si: 1588–1640 eV, and Mo: 169–199 eV. For the obtained Auger peaks of each element, the quantitative values ​​were obtained using peak intensity and relative sensitivity coefficients. The peak intensity was then calculated as the difference between the maximum and minimum peak values ​​(the so-called peak-to-peak intensity). In addition, the relative sensitivity coefficient can use the value provided by the device manufacturer.

[0170] For each measurement point, the P content (mol.%) at which the total content of P, S, C, Cr, Fe, Mn, Si, and Mo is set to 100 mol.% is defined as the P content (mol.%) at that measurement point. The arithmetic mean of the P content (mol.%) at all measurement points is defined as the grain boundary P amount P_seg. (mol.%). That is, in this embodiment, the P content P_seg. near the original austenite grain boundary refers to the P content (mol.%) obtained quantitatively by Auger electron spectroscopy analysis in the original austenite grain boundary section, where the total content of P, S, C, Cr, Fe, Mn, Si, and Mo is set to 100 mol.%. It should be noted that in this embodiment, the grain boundary P amount P_seg. (mol.%) is obtained by rounding the obtained value to the second decimal place. It should be noted that in this embodiment, Fn1(=(Mn+P_seg.) / (2.5Mo+GSN)) is obtained by rounding the fourth decimal place of the obtained value.

[0171] [SSC Resistance]

[0172] The steel of this embodiment has the above-described chemical composition and satisfies formula (1). As a result, the steel of this embodiment combines a yield strength of 125 ksi and excellent SSC resistance in high H2S environments. In this embodiment, "the steel has excellent SSC resistance" is defined as follows.

[0173] Specifically, in this embodiment, the SSC resistance of the steel is evaluated by an SSC resistance test performed in an H2S gas environment of 0.1 atm according to the method of NACE TM0177-2016 Method A and a four-point bending test performed in an H2S gas environment of 10 atm according to the method of NACE TM0316 (2016).

[0174] First, the SSC resistance test conducted in an H2S gas environment of 0.1 atm according to NACE TM0177-2016 Method A will be described. Round bar test pieces are made from the steel of this embodiment. The size of the round bar test piece is, for example, a diameter of 6.35 mm for the parallel portion and a length of 25.4 mm for the parallel portion. When the steel is a steel plate, the round bar test piece is made from the center of the plate thickness. In this case, the axial direction of the round bar test piece is set parallel to the rolling direction of the steel plate. When the steel is a steel pipe, the round bar test piece is made from the center of the wall thickness. In this case, the axial direction of the round bar test piece is set parallel to the pipe axis direction. When the steel is a round bar, the round bar test piece is made from the R / 2 position. In this case, the axial direction of the round bar test piece is set parallel to the axial direction of the round bar.

[0175] The prepared round bar test piece was subjected to a stress equivalent to 90% of the actual yield stress. A mixed aqueous solution of 5.0% by mass sodium chloride and 0.4% by mass sodium acetate (NACE solution B), adjusted to pH 3.5 with acetic acid, was used as the test solution. The test solution at 24°C was poured into the test vessel to immerse the stressed round bar test piece, thus creating a test bath. After degassing the test bath, a mixture of 0.1 atm H₂S gas and 0.9 atm CO₂ gas was blown into the test bath to saturate it. The test bath saturated with the mixed gas was maintained at 24°C for 720 hours.

[0176] Next, a four-point bending test performed in an H2S gas environment at 10 atm according to the method of NACE TM0316 (2016) will be described. Test pieces for the four-point bending test are made from the steel of this embodiment. The test piece is, for example, 75 mm in length, 10 mm in width, and 2 mm in thickness. When the steel is a steel plate, the test piece is made from the center of the plate thickness. In this case, the long side of the test piece is parallel to the rolling direction of the steel plate. When the steel is a steel pipe, the test piece is made from the center of the wall thickness. In this case, the long side of the test piece is parallel to the pipe axis direction. When the steel is a round bar, the test piece is made from the R / 2 position. In this case, the long side of the test piece is parallel to the axial direction of the round bar.

[0177] According to NACE TM0316 (2016), a stress equivalent to 90% of the actual yield stress was applied to the test piece through four-point bending. The stressed test piece, along with the test fixture, was sealed in an autoclave. A mixed aqueous solution of 5.0% by mass sodium chloride and 0.4% by mass sodium acetate, adjusted to pH 4.0 with acetic acid, was used as the test solution. The test solution was injected into the autoclave by immersion of the test piece. H2S gas was pressurized and introduced into the autoclave to saturate the test solution, forming a test bath. At this point, the H2S gas concentration was 10 atm. After sealing the autoclave, the test bath was maintained at 24°C, and the test piece was immersed in the test bath for 720 hours while stirring.

[0178] In this embodiment, if no cracks are detected after 720 hours in the SSC resistance test and four-point bending test performed under the above conditions, it is judged that "the steel has excellent SSC resistance". It should be noted that, in this specification, "no cracks detected" means that no cracks are detected when the test piece is observed with the naked eye after the test.

[0179] [Microstructure]

[0180] The microstructure of the steel in this embodiment is mainly composed of tempered martensite and tempered bainite. Specifically, the total volume fraction of tempered martensite and tempered bainite in the microstructure of the steel in this embodiment is 90% or more. The balance of the microstructure is, for example, ferrite or pearlite. In steel having the above chemical composition and a yield strength of 862 MPa or more and less than 965 MPa, and satisfying formula (1), a microstructure having a total volume fraction of tempered martensite and tempered bainite of 90% or more exhibits excellent SSC resistance. Therefore, in this embodiment, if a steel having the above chemical composition and a yield strength of 862 MPa or more and less than 965 MPa, and satisfying formula (1), exhibits excellent SSC resistance, then the microstructure of this steel is determined to be a total volume fraction of tempered martensite and tempered bainite of 90% or more.

[0181] It should be noted that the volume fractions of tempered martensite and tempered bainite can be obtained by observation using the following method. First, a test piece with a specific observation surface is prepared from the steel of this embodiment. When the steel is a sheet, a test piece is prepared from the center of the sheet thickness, with the surface including both the rolling direction and the sheet thickness direction as the observation surface. When the steel is a pipe, a test piece is prepared from the center of the wall thickness, with the surface including both the pipe axis direction and the pipe diameter direction as the observation surface. When the steel is a round bar, a test piece is prepared with the surface including the R / 2 position at the center and including both axial and radial directions as the observation surface.

[0182] After grinding the observation surface of the test piece to a mirror finish, it was immersed in a nitric acid-ethanol etching solution for approximately 10 seconds for etching-based tissue visualization. Using SEM, 10 fields of view were observed on the etched observation surface using secondary electron imaging. The field of view area was, for example, 0.01 mm². 2 (Magnification 1000x). Tempered martensite and tempered bainite are determined by contrast in each field of view. The area ratios of the determined tempered martensite and tempered bainite are calculated. The method for calculating the area ratios is not particularly limited and can be a known method. For example, the area ratios of tempered martensite and tempered bainite can be calculated through image analysis. In this embodiment, the arithmetic mean of the area ratios of tempered martensite and tempered bainite calculated in all fields of view is defined as the volume ratio of tempered martensite and tempered bainite.

[0183] [Shape of steel]

[0184] As described above, the shape of the steel used in this embodiment is not particularly limited. The steel can be, for example, steel pipe, steel plate, or round steel. When the steel is an oil well pipe, a wall thickness of 9 to 60 mm is preferred. Seamless steel pipe is more preferably used in this embodiment. When seamless steel pipe is used in this embodiment, even thick-walled seamless steel pipes with a wall thickness of 15 mm or more achieve a yield strength of 125 ksi and excellent resistance to SSC in high H2S environments.

[0185] [Manufacturing Method]

[0186] The manufacturing method of the steel according to this embodiment will be described. Hereinafter, as an example of the steel according to this embodiment, the manufacturing method of a seamless steel pipe will be described. The manufacturing method of a seamless steel pipe includes: a process of preparing a tube blank (preparation process); and a process of quenching and tempering the tube blank to produce a seamless steel pipe (quenching process and tempering process). It should be noted that the manufacturing method of this embodiment is not limited to the manufacturing method described below. Each process will be described in detail below.

[0187] [Preparation Process]

[0188] In the preparation process, intermediate steel with the above-mentioned chemical composition is prepared. As long as the intermediate steel has the above-mentioned chemical composition, the manufacturing method of the intermediate steel is not particularly limited. The intermediate steel referred to here is plate-shaped steel when the final product is steel plate, tube blank when the final product is steel pipe, and bar steel with a circular cross-section perpendicular to the axial direction when the final product is round steel.

[0189] The preparation process may include: the process of preparing the billet (bill preparation process); and the process of hot working the billet to manufacture intermediate steel (hot working process). The following details the case including the billet preparation process and the hot working process.

[0190] [Burnt material preparation process]

[0191] In the billet preparation process, billets are manufactured using molten steel with the aforementioned chemical composition. The method of billet manufacturing is not particularly limited and can be any known method. Specifically, molten steel can be used to manufacture cast billets (slabs, large billets, or small billets) through continuous casting. Molten steel can also be used to manufacture ingots through ingot casting. Small billets can also be manufactured by initial rolling slabs, large billets, or ingots as needed. Billets (slabs, large billets, or small billets) are manufactured through the above processes.

[0192] [Heat treatment process]

[0193] In the hot working process, the prepared billet is hot-worked to produce intermediate steel. When the steel is a seamless steel pipe, the intermediate steel is equivalent to a pipe blank. First, a small square billet is heated in a furnace. The heating temperature is not particularly limited, for example, 1100~1300℃. The small square billet, removed from the furnace, is then hot-worked to produce a pipe blank (seamless steel pipe). The hot working method is not particularly limited and can be a known method.

[0194] There are no particular limitations on the hot working method. When the intermediate steel is a tube blank, the Mannesmann / mandrel method is preferred for hot working to manufacture the tube blank. In this case, the heated solid round steel billet is pierced and rolled using a piercing mill to produce a hollow round steel billet. The piercing ratio is not particularly limited in the case of piercing rolling, and is for example, 1.0 to 4.0. The pierced and rolled round steel billet, i.e., the hollow round steel billet, is further hot rolled using a mandrel-type seamless tube mill, reducing mill, sizing mill, etc., to manufacture a tube blank.

[0195] Preferably, in the stretch rolling of this embodiment, the temperature of the hollow round billet is kept below 1100°C. More specifically, in this embodiment, it is preferable to keep the temperature of the hollow round billet at the inlet side of the stretch rolling mill (e.g., a mandrel-type seamless tube mill) below 1100°C. If the temperature of the hollow round billet is below 1100°C, strain is easily generated in the hollow round billet during stretch rolling. In this case, the original γ grains are refined in the microstructure of the hollow round billet, and the enrichment of P towards the original γ grain boundaries is easily mitigated. As a result, the amount of P at grain boundaries, P_seg., can be reduced in the manufactured steel. It should be noted that if the temperature of the hollow round billet at the inlet side of the stretch rolling mill is too low, the load on the stretch rolling mill and the sizing mill will increase. Therefore, the lower limit of the temperature of the hollow round billet at the inlet side of the stretch rolling mill is preferably set to 950°C or higher.

[0196] Preferably, in the stretch rolling of this embodiment, the initial rolling degree of the stretch rolling is 24.5% or more. Here, in the stretch rolling of this embodiment, a stretch rolling mill composed of multiple rolling mill stands can also be used to perform stretch rolling. In this case, each rolling mill stand has multiple rolls arranged around the rolling line through which the hollow round steel billet passes, and arranged along the rolling line. The number of rolls in the rolling mill stand is not limited; a two-roll rolling mill stand or a three-roll rolling mill stand can be used.

[0197] Specifically, "the initial rolling in stretch rolling" refers to the rolling performed by the first and second stands of a stretch rolling mill arranged along the rolling line of the hollow round billet when stretch rolling is performed using a two-roll mill. Similarly, when stretch rolling is performed using a three-roll mill, it refers to the rolling performed by the first and second stands arranged along the rolling line of the hollow round billet. That is, when using a stretch rolling mill composed of multiple mill stands, it is preferable that the machining degree Rm (%) in the first and second stands of the stretch rolling mill is 24.5% or more.

[0198] Hereinafter, in this specification, the "machining degree Rm (%) in the first and second stands of the stretching mill" will also be referred to as "the primary machining degree Rm (%) of stretching rolling". More specifically, in the case of using a stretching mill consisting of multiple mill stands, the primary machining degree Rm (%) of stretching rolling is defined by the following formula (A).

[0199] The initial processing degree of stretch rolling, Rm (%), is calculated as follows: 100 × {(wall thickness of the hollow tube billet after piercing rolling - wall thickness of the hollow tube billet after the second stand of the stretch mill) / wall thickness of the hollow tube billet after piercing rolling} (A)

[0200] If the initial processing degree Rm of the stretch rolling is 24.5% or more, strain is easily generated in the hollow round billet during stretch rolling. In this case, the original γ grains in the microstructure of the hollow round billet are refined, and the enrichment of P at the original γ grain boundaries is easily mitigated. As a result, the amount of P at grain boundaries P_seg. can be reduced in the manufactured steel. Therefore, in this embodiment, it is preferable to make the initial processing degree of stretch rolling 24.5% or more. It should be noted that there is no particular upper limit to the initial processing degree of stretch rolling, for example, it is 50.0%.

[0201] It should be noted that after stretch rolling, sizing rolling or reduction rolling can be performed. These hot rolling processes can be carried out using known equipment and methods, without particular limitations. Furthermore, tube blanks manufactured through hot working can be air-cooled (as-rolled), or they can be quenched directly after hot working without cooling to room temperature, or they can be quenched after reheating (reheating) following hot working. The quenching and tempering processes are described in detail below.

[0202] [Quenching process]

[0203] In the quenching process, the prepared intermediate steel (tube blank) is quenched. In this specification, "quenching" refers to the rapid cooling of intermediate steel with a point A3 or higher. If the quenching temperature is too high, the original γ-grains become coarser, and the steel's SSC resistance may sometimes decrease. Therefore, the quenching temperature is preferably 850~1000℃. It should be noted that, in this specification, the quenching temperature refers to the surface temperature of the intermediate steel measured by a thermometer installed on the outlet side of the device where the final hot working is performed, when quenching is performed directly after hot working. Furthermore, when quenching is performed after reheating or reheating following hot working, the quenching temperature is equivalent to the temperature of the furnace where the reheating or reheating is performed.

[0204] Quenching methods include, for example, continuously cooling the intermediate steel (tube blank) from the quenching start temperature, causing the surface temperature of the tube blank to decrease continuously. There are no particular limitations on the continuous cooling method; any known method can be used. Examples of continuous cooling methods include immersing the tube blank in a water bath for cooling, or accelerating the cooling of the tube blank through water spraying or mist cooling.

[0205] If the cooling rate during quenching is too slow, the microstructure of tempered martensite and tempered bainite may not be formed. In this case, the mechanical properties specified in this embodiment (yield strength of 125 ksi) cannot be obtained. Consequently, the steel does not achieve excellent SSC resistance. Therefore, as described above, in the steel manufacturing method of this embodiment, the intermediate steel is rapidly cooled during quenching. Specifically, in the quenching process, the average cooling rate of the intermediate steel (tube blank) within the surface temperature range of 800~500°C during quenching is defined as the quenching cooling rate CR. 800-500 More specifically, the cooling rate CR during quenching 800-500 The temperature is determined based on the part of the intermediate steel that is cooled most slowly within its cross-section (e.g., the center of the intermediate steel thickness in the case of forced cooling of both surfaces).

[0206] Preferred cooling rate CR during quenching 800-500 The quenching rate is 300℃ / minute or higher. A more preferred cooling rate during quenching is CR.800-500 The lower limit is 450℃ / min, more preferably 600℃ / min. The cooling rate CR during quenching... 800-500 There is no specific upper limit, such as 60,000℃ / minute.

[0207] Preferably, the billet is heated multiple times in the austenitic region before quenching. In this case, the austenitic grains are refined, thus improving the steel's resistance to sintering steel (SSC). This heating can be repeated by performing multiple quenching processes, or by performing normalizing and quenching. Alternatively, quenching and tempering (described later) can be combined and performed multiple times. That is, multiple quenching and tempering processes can also be performed. In this case, the steel's resistance to SSC is further improved. The tempering process will be described in detail below.

[0208] [Tempering process]

[0209] In the tempering process, the intermediate steel that has undergone the above-mentioned quenching is tempered. In this specification, "tempering" refers to tempering the quenched intermediate steel at a temperature less than A. c1 The intermediate steel is then reheated and held at a specified temperature. Here, the tempering temperature corresponds to the temperature of the heat treatment furnace at which the quenched intermediate steel is heated and held. The tempering time refers to the time from when the intermediate steel reaches the specified tempering temperature until it is removed from the heat treatment furnace.

[0210] The tempering temperature is adjusted appropriately based on the chemical composition of the steel and the desired yield strength. Specifically, for intermediate steel with the chemical composition of this embodiment, the tempering temperature is adjusted to achieve a yield strength of 125 ksi (862 MPa or higher and less than 965 MPa). In the tempering process of this embodiment, a tempering temperature of 600–700°C is preferred. Furthermore, in the tempering process of this embodiment, the tempering time is preferably set to 10–240 minutes.

[0211] The steel of this embodiment can be manufactured using the above manufacturing method. However, as described above, the manufacturing method is only one example, and other manufacturing methods can also be used. The present invention will be further described in detail below through examples.

[0212] Example

[0213] Molten steel with the chemical compositions shown in Tables 1A and 1B is produced. It should be noted that the "-" in Table 1B indicates that the content of each element is at the impurity level. Specifically, the Cu, Ni, W, and Zr contents in Test No. 1 are rounded to the third decimal place to 0%. The Mg and REM contents in Test No. 1 are rounded to the fifth decimal place to 0%.

[0214] [Table 1A]

[0215]

[0216] [Table 1B]

[0217]

[0218] Using molten steel from each test number, solid round billets with the diameters listed in Table 2 were manufactured by continuous casting. The solid round billets from each test number were heated and pierced to produce hollow round billets. The hollow round billets after piercing were then subjected to stretch rolling and sizing rolling to produce tube blanks for each test number. The outer diameter (mm) and wall thickness (mm) of the tube blanks for each test number are shown in Table 2. In this embodiment, stretch rolling was performed using a mandrel-type seamless tube mill with a two-roll configuration. In each test number, the surface temperature of the hollow round billet at the entry point of the stretch mill (mandrel-type seamless tube mill) is shown in the "Entry Temperature (°C)" column of Table 2. It should be noted that the temperature of the hollow round billet was measured using a non-contact thermometer. Furthermore, in each test number, the initial processing degree Rm (%) of the stretch rolling (processing degree (%) in the first and second stands of the mandrel-type seamless tube mill) is shown in the "Rm (%)" column of Table 2.

[0219] [Table 2]

[0220]

[0221] For the tube blanks of each test number, after heating at the temperature (°C) and time (minutes) recorded in Table 2, rapid quenching was performed. It should be noted that the cooling rate (CR) during quenching... 800-500 All temperatures were maintained at 300~60000℃ / minute. Then, tempering was performed at the temperatures (℃) and holding times (minutes) recorded in Table 2. Seamless steel pipes for each test number were manufactured using the above method.

[0222] [Evaluation Test]

[0223] The following tensile tests, original γ grain observation tests, grain boundary P content determination tests, and SSC resistance tests were performed on the seamless steel pipes manufactured for each test number.

[0224] [Tension Test]

[0225] Round bar test specimens with a parallel section diameter of 8.9 mm and a gauge length of 35.6 mm were prepared from the central portion of the wall thickness of seamless steel pipes for each test number using the method described above. Tensile tests were performed on the prepared round bar test specimens at room temperature (25°C) in the atmosphere according to ASTM E8 / E8M (2022). The stress at 0.7% elongation obtained through the tensile test was defined as the yield strength (MPa). Furthermore, the maximum stress at uniform elongation obtained through the tensile test was defined as the tensile strength (MPa). The obtained yield strength (MPa) is shown in the "YS (MPa)" column of Table 3. The obtained tensile strength (MPa) is shown in the "TS (MPa)" column of Table 3.

[0226] [Table 3]

[0227]

[0228] [Original γ-grain observation experiment]

[0229] From the center of the wall thickness of each seamless steel pipe of each test number, test pieces were prepared using the method described above, with the observation surface being a plane encompassing both the pipe axis and pipe diameter directions. The prepared test pieces were then etched using the method described above to reveal the original γ grain boundaries. For a 100mm diameter... 2 The original γ grains were observed using an optical microscope on a 10mm × 10mm observation surface. Based on the cutting method according to JIS G 0551 (2020), the grain size number (GSN) of the original γ grains was determined. The obtained grain size numbers (GSN) of the original γ grains are shown in the "Original γ Grain Size Number (GSN)" column of Table 3.

[0230] [Grain Boundary Phosphorus Content Measurement Test]

[0231] From the central portion of the wall thickness of seamless steel pipes of each test number, notched round bar test pieces with a diameter of 3 mm and an axial length of 17 mm were prepared using the method described above. In the notched round bar test pieces, a V-shaped notch with a depth of 0.7 mm was formed along the entire circumference of the round bar at the central portion of the axial length. The notched round bar test pieces were subjected to impact fracture using the method described above to obtain the original γ grain boundary cross-section. Furthermore, 10 measurement points were determined from each of the obtained original γ grain boundary cross-sections using the method described above. For the determined measurement points, elemental concentration analysis based on Auger electron spectroscopy was performed using the method described above to obtain the P content (mol.%) at each measurement point. The arithmetic mean of the P content (mol.%) at the 10 measurement points was defined as the grain boundary P amount P_seg. (mol.%). The obtained grain boundary P amount P_seg. (mol.%) is shown in Table 3.

[0232] Furthermore, for each test number, Fn1 (=(Mn+P_seg.) / (2.5Mo+GSN)) was calculated from the Mn content (mass%), Mo content (mass%), the original γ grain grain size number GSN, and the grain boundary P content P_seg. (mol.%). The obtained Fn1 is shown in Table 3.

[0233] [SSC Resistance Test]

[0234] For the seamless steel pipes of each test number, the SSC resistance test was carried out in an H2S gas environment of 0.1 atm according to the method of NACETM0177-2016 Method A, and the four-point bending test was carried out in an H2S gas environment of 10 atm according to the method of NACETM0316 (2016).

[0235] First, round bar test pieces with a parallel section diameter of 6.35 mm and a parallel section length of 25.4 mm were prepared from the central portion of the wall thickness of the seamless steel pipe for each test number using the method described above. For the prepared round bar test pieces, a stress equivalent to 90% of the actual yield stress was applied, according to NACE TM0316 (2016). A test solution (a mixed aqueous solution of 5.0 wt% sodium chloride and 0.4 wt% sodium acetate) at 24°C was injected into the test vessel to immerse the stressed round bar test pieces, thus creating a test bath. After degassing the test bath, a mixture of 0.1 atm H2S gas and 0.9 atm CO2 gas was blown into the test bath to saturate it. The test bath saturated with the mixed gas was maintained at 24°C for 720 hours.

[0236] The test pieces were visually inspected after 720 hours. If no cracks were found, the test pieces were judged to have excellent SSC resistance ("EX" in the "0.1 atm H2S" column of Table 3). Conversely, if cracks were found, the test pieces were judged to have non-excellent SSC resistance ("NA" in the "0.1 atm H2S" column of Table 3).

[0237] Next, three test pieces, each 75 mm long, 10 mm wide, and 2 mm thick, were prepared from the center of the wall thickness of the seamless steel pipe for each test number using the method described above. Each test piece was subjected to a four-point bending test, with a stress equivalent to 90% of the actual yield stress. In an autoclave, the test pieces were immersed in a test solution (a mixed aqueous solution of 5.0% sodium chloride and 0.4% sodium acetate, adjusted to pH 4.0 with acetic acid). The autoclave was pressurized with 10 atm of H₂S gas to saturate the test solution, creating a test bath. After sealing the autoclave, the test bath was maintained at 24°C, and the test pieces were immersed for 720 hours while the bath was stirred.

[0238] The test pieces were visually inspected after holding. The number of cracks confirmed in each of the three test pieces was counted and defined as "SSC generation count (cracks)". The SSC generation count (cracks) obtained under a 10 atm H2S gas environment is shown in the "10 atm H2S" column of Table 3.

[0239] [Evaluation Results]

[0240] Referring to Tables 1A, 1B, 2, and 3, the seamless steel pipes tested (numbers 1-18) had appropriate chemical compositions, yield strengths above 862 MPa and below 965 MPa, and Fn1 values ​​below 0.125. As a result, these seamless steel pipes exhibited zero SSC formation in a 10 atm H2S gas environment, demonstrating excellent SSC resistance even in high H2S conditions.

[0241] On the other hand, the seamless steel pipe in test number 19 had excessively high Mn and Fn1 content. As a result, this seamless steel pipe produced more than one SSC in a 10 atm H2S gas environment, and did not exhibit excellent SSC resistance in high H2S environments.

[0242] The seamless steel pipe in test number 20 had too low a Mo content and too high a Fn1 content. As a result, the seamless steel pipe produced more than one SSC in a 10 atm H2S gas environment, and did not have excellent SSC resistance in a high H2S environment.

[0243] The seamless steel pipes tested in experiments 21 and 22 had excessively high Mn content, excessively low Mo content, and excessively high Fn1 content. As a result, these seamless steel pipes produced more than one SSC (Self-Strain Scrap) in a 10 atm H2S gas environment, and did not exhibit excellent SSC resistance in high H2S environments.

[0244] The temperature of the hollow round billet during the tensile rolling of seamless steel pipes in tests 23-27 was too high, resulting in an excessively high Fn1. As a result, these seamless steel pipes exhibited more than one SSC (Superficial Staining Component) in a 10 atm H2S gas environment, and did not demonstrate excellent SSC resistance in high H2S environments.

[0245] The initial tensile rolling finish Rm of the seamless steel pipes tested (numbers 28-31) was too small, and Fn1 was too high. As a result, these seamless steel pipes produced more than one SSC (Superficial Strain Detection) in a 10 atm H2S gas environment, and did not exhibit excellent SSC resistance in high H2S environments.

[0246] The Fn1 of seamless steel pipes tested (numbers 32-34) was too high. As a result, these seamless steel pipes produced more than one SSC (superficial sclerolysis) in a 10 atm H2S gas environment, and did not exhibit excellent SSC resistance in high H2S environments.

[0247] The embodiments of this disclosure have been described above. However, the above embodiments are merely illustrative examples for implementing this disclosure. Therefore, this disclosure is not limited to the above embodiments, and appropriate modifications can be made to the above embodiments without departing from its spirit.

Claims

1. A type of steel, which, in terms of mass%, is C: Above 0.15% and below 0.30% Si: 0.05~1.00% Mn: ≥0.05% and <0.30% P: below 0.020% S: Below 0.0050% Cr:0.10~1.00%、 Mo: 0.85~2.50%, Ti: 0.002~0.020% Nb: 0.002~0.050% V:0.01~0.30%、 Ca: 0.0001~0.0030% B:0.0005~0.0050%、 Al:0.005~0.100%、 N: below 0.0050% O: Below 0.0020% Cu: 0~0.50%, Ni: 0~0.50% W:0~1.00%、 Zr:0~0.50%、 Mg: 0~0.0100% Rare earth elements: 0~0.0100%, and The balance consists of Fe and impurities. The yield strength of the steel is above 862 MPa and less than 965 MPa. The content of the elements, the grain size number GSN of the original austenite grains in the microstructure, and the P content P_seg near the original austenite grain boundaries satisfy equation (1). (Mn+P_seg.) / (2.5Mo+GSN)≤0.125 (1) Here, the element symbols in equation (1) are substituted with the corresponding element content in the unit: mass% In addition, in formula (1), the P content near the original austenite grain boundary is mol.% at P_seg. and the grain size number of the original austenite grain is substituted at GSN in formula (1).

2. The steel according to claim 1, wherein it contains selected... Cu: 0.01~0.50%, Ni: 0.01~0.50% W:0.01~1.00%、 Zr:0.01~0.50%、 Mg: 0.0001~0.0100%, and Rare earth elements: one or more elements in a group consisting of 0.0001 to 0.0100%.

3. The steel according to claim 1 or 2, wherein, The steel is a seamless steel pipe.

Citation Information

Patent Citations

  • Nitride based inclusion form controlled steel

    JP2006028612A

  • Material for high-strength oil well steel tube and method of manufacturing high-strength oil well steel tube using the material

    JP2017166060A